Exosomal cellular prion protein drives fibrillization of amyloid beta and counteracts amyloid beta‐mediated neurotoxicity. Issue 1 (2nd March 2016) - Falker, Clemens; Hartmann, Alexander; Guett, Inga; Dohler, Frank; Altmeppen, Hermann; Betzel, Christian; Schubert, Robin; Thurm, Dana; Wegwitz, Florian; Joshi, Pooja; Verderio, Claudia; Krasemann, Susanne; et al.
Abstract: Alzheimer's disease is a common neurodegenerative, progressive, and fatal disorder. Generation and deposition of amyloid beta (Aβ) peptides associate with its pathogenesis and small soluble Aβ oligomers show the most pronounced neurotoxic effects and correlate with disease initiation and progression. Recent findings showed that Aβ oligomers bind to the cellular prion protein (PrP C ) eliciting neurotoxic effects. The role of exosomes, small extracellular vesicles of endosomal origin, in Alzheimer's disease is only poorly understood. Besides serving as disease biomarkers they may promote Aβ plaque formation, decrease Aβ‐mediated synaptotoxicity, and enhance Aβ clearance. Here, we explore how exosomal PrP C connects to protective functions attributed to exosomes in Alzheimer's disease. To achieve this, we generated a mouse neuroblastoma PrP C knockout cell line using transcription activator‐like effector nucleases. Using these, as well as SH‐SY5Y human neuroblastoma cells, we show that PrP C is highly enriched on exosomes and that exosomes bind amyloid beta via PrP C . Exosomes showed highest binding affinity for dimeric, pentameric, and oligomeric Aβ species. Thioflavin T assays revealed that exosomal PrP C accelerates fibrillization of amyloid beta, thereby reducing neurotoxic effects imparted by oligomeric Aβ. Our study provides further evidence for a protective role of exosomes in Aβ‐mediated neurodegeneration and highlights the importance of exosomal PrP C in molecular mechanisms of Alzheimer's disease. We show that the prion protein (PrP C ) on exosomes captures neurotoxic species of amyloid beta (Aβ) promoting its fibrillization. Our study provides evidence for a protective role of exosomes in Alzheimer`s disease and suggests that, depending on its membrane topology, PrP C holds a dual function: when expressed at the neuronal surface it acts as receptor for Aβ leading to neurotoxic signaling, whereas it detoxifies Aβ when present on exosomes. This provides further support for key roles of PrP C in Alzheimer's disease. Read theEditorial Highlight for this article on page9 . Cover Image for this issue: doi:10.1111/jnc.13312 . Abstract : We show that the prion protein (PrP C ) on exosomes captures neurotoxic species of amyloid beta (Aβ) promoting its fibrillization. Our study provides evidence for a protective role of exosomes in Alzheimer`s disease and suggests that, depending on its membrane topology, PrP C holds a dual function: when expressed at the neuronal surface it acts as receptor for Aβ leading to neurotoxic signaling, whereas it detoxifies Aβ when present on exosomes. This provides further support for key roles of PrP C in Alzheimer's disease. Read theEditorial Highlight for this article on page9 . Cover Image for this issue: doi:10.1111/jnc.13312 .